What are the needs of beginning teachers in primary education and how can mentors help them? - Badescu, Ruxandra Florentina (Technium Social Sciences Journal, 2024)
Beginning teachers face numerous challenges when entering the profession. Their needs range from classroom management to emotional support, and mentors play a crucial role in addressing these challenges. This article explores the primary needs of novice teachers and how effective mentoring can help them navigate their first years in primary education. Drawing on both international research and Romanian educational practices, this paper highlights the importance of structured, supportive mentorship programs in shaping successful teaching careers.